Discovery and Imitation of Export Products and the Role of Existing Exporters in Korean Manufacturing - Chin Hee Hahn (KDI Journal of Economic Policy, 2019)
This paper empirically examines what role of existing exporters play in the discovery of new export products and whether there are evidence of spillovers from export discovery. We find that existing exporters are more likely to discover new export products than non-exporters. We also find evidence of export discovery spillovers; export discovery of a product by some plants had an effect of increasing the probability of subsequent export market penetration of the same product by other plants. Export discovery spillovers are found to be stronger among geographically closely located plants. We argue that information spillovers is a part of the story: you learn from your neighboring discoverers about the profitability of potentially exportable products.
Keywords: F14; F61; O12; 330; Export Discovery; Imitation; Export Spillovers